Review of Zoning Regulations for Seismic Area on the Southwest Coast of Sumatra, Indonesia - Akhmad Akhmad; Sinung Mufti Hangabei (Faculty of Law, Universitas Sebelas Maret, 2023)
The Indonesian region is one of the countries with high seismicity because it is located on the Ring of Fire. This article describes and analyzes regulations regarding earthquake-prone areas on the southwest coast of Sumatra Island, especially in Bengkulu. Data related to earthquake and disaster was taken using the literature method from several previous research results and disaster reports from government agencies. The results of the study show that the potential for earthquake hazard is dominating Bengkulu City. Several policies and regulations regarding urban land use were issued, but they must be further aligned with the objective of earthquake disaster mitigation. Almost all areas are located in moderate seismic hazard areas, so general rules and parameters are needed for classification structures; this is a must to ensure that in the event of an earthquake, human life is protected. Detailed spatial plans and zoning regulations become important documents that can regulate spatial use in detail, accompanied by calculations related to the density and environmental conditions of the area given spatial provisions.